2022
DOI: 10.3389/fmed.2022.803069
|View full text |Cite
|
Sign up to set email alerts
|

Self-Regulated Learning Practice of Undergraduate Students in Health Professions Programs

Abstract: BackgroundUniversity students are expected to take charge of their learning without being dependent on teachers. Self-regulated learning (SRL) is the process by which students direct their learning to achieve their set targets and goals in a timely and controlled manner. This study was undertaken to explore the practice of SRL by undergraduate students from different programs in a health science focused university during COVID-19 pandemic.MethodThirty-three undergraduate students of five health professions edu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 51 publications
1
3
0
1
Order By: Relevance
“…Rui et al emphasized that the development of metacognitive strategy enhanced active learning among students [11]. In line with our results, Chitra et al found that the practice of SRL strategies enabled students to be more successful in their careers [12]. Siddiqui et al have reported that SRL strategies not only enhance medical students' performance as care providers and lifelong learners but also equip them to manage difficult situations by enhancing their leadership qualities, communication, and decision-making skills [13].…”
Section: Discussionsupporting
confidence: 87%
“…Rui et al emphasized that the development of metacognitive strategy enhanced active learning among students [11]. In line with our results, Chitra et al found that the practice of SRL strategies enabled students to be more successful in their careers [12]. Siddiqui et al have reported that SRL strategies not only enhance medical students' performance as care providers and lifelong learners but also equip them to manage difficult situations by enhancing their leadership qualities, communication, and decision-making skills [13].…”
Section: Discussionsupporting
confidence: 87%
“…The students' self-directed learning levels were also reported to be above average. The findings of previous studies investigating the self-directed learning levels of university students mostly indicate that university students have above-average SRL levels (Argun, 2021;Askin, 2015;Askin & Demirel, 2018;Chitra et al, 2022;Holzweber, 2019). It seems that the fact that university-level students as adults have various learning experiences, either easy or difficult, and face obstacles (Holzweber, 2019) throughout their educational life most likely provides them with skills such as being aware of their own learning styles or monitoring their progress.…”
Section: Discussionmentioning
confidence: 96%
“…For the purposes of the intervention, and to make the steps of self-regulated learning more relatable and actionable for medical students, the three phases were simplified to represent the core principles of self-regulated learning including 1) goal setting, 2) applying evidence-based learning strategies, and 3) reflection. This simplified model has also been used in prior studies involving self-regulated learning among medical students [ 17 ]. In this study, evidence-based learning strategies refers to methods for learning which have been shown to improve long-term retention of learned material including self-quizzing, consolidation, and interleaving [ 18 ].…”
Section: Methodsmentioning
confidence: 99%